Association Between SARS-CoV-2 RNAemia and Postacute Sequelae of COVID-19. (25th December 2021) - Ram-Mohan, Nikhil; Kim, David; Rogers, Angela J; Blish, Catherine A; Nadeau, Kari C; Blomkalns, Andra L; Yang, Samuel
Abstract: Determinants of Post-Acute Sequelae of COVID-19 are not known. Here we show that 83.3% of patients with viral RNA in blood (RNAemia) at presentation were symptomatic in the post-acute phase. RNAemia at presentation successfully predicted PASC, independent of patient demographics, worst disease severity, and length of symptoms.